2021
DOI: 10.3390/ijerph18083909
|View full text |Cite
|
Sign up to set email alerts
|

Device-Measured and Self-Reported Active Travel Associations with Cardiovascular Disease Risk Factors in an Ethnically Diverse Sample of Adults

Abstract: Active travel (AT) provides an opportunity to alleviate the physical inactivity and climate crises contributing to the global chronic disease burden, including cardiovascular diseases (CVD). Though AT shows promising links to reduced CVD risk, prior studies relied on self-reported AT assessment. In the present study, device-measured and self-reported AT were compared across population subgroups and relationships with CVD risk biomarkers were evaluated for both measures. The study recruited an ethnically divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 75 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…The mean age of the participants was 54.1 (SD 12.35) years, with a range of 15 to 98 years, where mean age could be retrieved from the data set (110/122, 90.2%). Data sets were identified in 5 continents, with the majority being retrieved from Europe and North America (n=85 data sets) [ 5 , 21 , 22 , 24 , 25 , 28 , 31 - 36 , 39 - 45 , 48 - 50 , 52 , 55 - 58 , 60 - 63 , 66 , 67 , 70 - 72 ,​ 74 , 75 , 77 - 80 , 82 , 84 - 86 , 89 , 91 - 96 , 98 - 102 , 104 , 105 , 107 - 109 , 111 - 115 , 117 ,​ 119 , 121 , 124 , 125 , 128 , 129 , 131 , 132 , 140 ]. A wide range of health markers have been collected, with most studies measuring height (119/122, 97.5%), body mass (119/122, 97.5%), and blood pressure (82/122, 67.2%).…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of the participants was 54.1 (SD 12.35) years, with a range of 15 to 98 years, where mean age could be retrieved from the data set (110/122, 90.2%). Data sets were identified in 5 continents, with the majority being retrieved from Europe and North America (n=85 data sets) [ 5 , 21 , 22 , 24 , 25 , 28 , 31 - 36 , 39 - 45 , 48 - 50 , 52 , 55 - 58 , 60 - 63 , 66 , 67 , 70 - 72 ,​ 74 , 75 , 77 - 80 , 82 , 84 - 86 , 89 , 91 - 96 , 98 - 102 , 104 , 105 , 107 - 109 , 111 - 115 , 117 ,​ 119 , 121 , 124 , 125 , 128 , 129 , 131 , 132 , 140 ]. A wide range of health markers have been collected, with most studies measuring height (119/122, 97.5%), body mass (119/122, 97.5%), and blood pressure (82/122, 67.2%).…”
Section: Resultsmentioning
confidence: 99%
“…It can also be due to difference in personal mobility such as active travel (i.e., biking and walking to get from place to place). Previously, it was shown that Non-Hispanics had more device-based active travel minutes, derived from accelerometer and GPS devices, than Hispanics/Latinos ( Crist et al, 2021 ). This unexpected finding is not consistent with previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…Street green vision is a method of capturing and identifying street-level images to determine the exposure of greenery in a neighborhood, and it provides an objective view of the green environment from a human perspective (13). Studies have found that higher street greenness is associated with a higher propensity for older adults to exercise (12), which in turn reduces obesity (59,60).…”
Section: Literature Review 21 Research Related To the Impact Of The B...mentioning
confidence: 99%